Still – these are Heeltaps (on the topic of heeled footwear in the Middle Ages) - Krylasova Natalia B.; Smertin Andrey R. (Поволжская археология, 2023)
Among materials from the Volga Bulgaria of the 11th–13th centuries, as well as the territories under Bulgarian rule, forged oval-shaped articles reminiscent of shoe heel section can be found. There is no unanimous opinion concerning these finds among researchers. A considerable assortment of these items was excavated at the Rozhdestvensky settlement in the Perm Region. Analysis showed that they were made of raw steel, with the base a half-oval plate with folded edges and with three apertures for little cylinder-capped nails, the cap standing out on the item’s surface.Cylinder nuts were put on the nails from the inner side and were forged when heated. The nuts held a leather plate in place, which was thought to be a lower lift of the built-up heel. Thus the items under scrutiny served as heeltaps. It is recognized that first heels appeared in the 9th century as a feature of Persian riders’ footwear. They helped to hold the feet firmly in the stirrups when the warrior stood on the stirrups to shoot with a bow or to slash with a sabre more efficiently. Volga Bulgaria had close relations with Iran, therefore Bulgar riders may well have adopted a new kind of footwear. Even though there is no other evidence save the iron heeltaps, it may be assumed that heeled footwear was adopted in Volga Bulgaria sooner than in Rus and European countries, where it happened in the 16th century. This fact is essential for both studying the footwear of the Middle Ages and tactics of fighting on horseback.